Innovation of Management Strategies in the Pre-profesisonal Practical Process (Docentes 2.0 Journal, 2022)
Pre-professional internships are considered the continuity of the contact that students make with the work context. It is a meeting where development is favored, and the necessary skills to face the real problems of the professional field are consolidated. The objective of the present investigation was to improve the management strategies in the pre-professional practical process of the San Francisco de Asís Private University, El Alto Branch. The present study was contemplated under the sequential exploratory method, paradigm of pragmatism, hybrid approach, exploratory-descriptive type, and non-experimental design. It was developed with a non-probabilistic sample of the intentional kind, with inclusion criteria of 24 students and five teachers. The technique of recording the observation of pre-professional reports, vice-chancellor's office, and focus group were used. The quantitative data analysis was carried out through the arithmetic mean, based on obtaining averages and qualitative information based on focus groups and documentary reviews. Finally, the study allowed to have a detailed plan linking, the university with institutions related to each career of the academic offer of the USFA university. Also, the work is entitled to generate new inter-institutional relationships, increasing the options of spaces where students can develop their pre-professional practices.
Keywords: Innovation; practical pre-professional process; management strategies